2005
DOI: 10.1039/b412281j
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational predissociation spectra and hydrogen-bond topologies of H+(H2O)9–11

Abstract: Vibrational predissociation spectra of protonated water clusters H+(H2O)n, n = 9-11, are presented. Examination of the spectra in the free-OH stretching region revealed predominance of a single absorption band at approximately 3690 cm(-1) for three-coordinate H2O acting as a double-proton-acceptor/single-proton-donor in the n = 11 cluster. In contrast, the intensity of the absorption band of two-coordinate H2O acting as a single-proton-acceptor/single-proton-donor at approximately 3715 cm(-1) decreases with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
3
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 50 publications
5
98
3
2
Order By: Relevance
“…It is will known that H + (H 2 O) 6 is the smallest protonated water cluster that can carry a fully solvated Zundel type hydronium and very recently Headrick et al have shown conclusive evidences on its existence in Ar-attached protonated water clusters 7 . Previous IR spectra, however, always indicate that bare H + (H 2 O) 6 is a mixture of two topological isomers even temperature as low as 77K. This raises concerns regarding the role of the attached Ar atom on the relative stability of different structural isomers -which will be addressed in this article.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is will known that H + (H 2 O) 6 is the smallest protonated water cluster that can carry a fully solvated Zundel type hydronium and very recently Headrick et al have shown conclusive evidences on its existence in Ar-attached protonated water clusters 7 . Previous IR spectra, however, always indicate that bare H + (H 2 O) 6 is a mixture of two topological isomers even temperature as low as 77K. This raises concerns regarding the role of the attached Ar atom on the relative stability of different structural isomers -which will be addressed in this article.…”
Section: Introductionmentioning
confidence: 99%
“…For H + (H 2 O) 6 , MP2 method with aug-cc-pvDZ (denote as MaDZ) is the highest level ab initio methods with the largest basis set applicable for such system size. In addition, it has been shown that MaDZ allows an accurate characterization of smaller clusters 13,17,18 .…”
Section: Electronic Energy (Ee) and Zero-point Energy With Harmonic Omentioning
confidence: 99%
See 3 more Smart Citations